The North-West European shelf seas : the sea bed and the sea in motion. - Banner, F. T. (Frederick Thomas), 1930-2006; Collins, M. B.; Massie, K. S. (Elsevier oceanography series ;, 1980)
Physical and Chemical Oceanography, and Physical Resources.